DIGITAL LITERACY IN CHEMISTRY LEARNING: SYSTEMATIC LITERATURE REVIEW - Zidan, Muhammad Rifqi; Syarofie, Icha Sabina; Silfianah, Ifah (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2025)
Digital literacy can be utilized in chemistry learning to support the learning process and improve students' understanding and learning outcomes about chemistry. This study aims to analyze digital literacy in chemistry learning in terms of the digital literacy profile of students and college students, the influence of digital literacy on learning outcomes, learning models, and media used to improve digital literacy. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) is a technique used to analyze research results from articles that have been published on students' digital literacy in chemistry in national and international journals as many as 20 articles with a span of 2019 to 2024. The analysis results concluded that the digital literacy skills of students and college students are very diverse. There is an influence on learning outcomes with the use of media and learning models to improve digital literacy that supports the chemistry learning process